Serum leptin levels in relation to circulating cytokines, chemokines, adhesion molecules and angiogenic factors in normal pregnancy and preeclampsia - Karádi István; Bekő Gabriella; Walentin Szilvia; Szarka András; Molvarec Attila; Prohászka Zoltán; Rigó Jr János (BMC, 2011)
Abstract Objective In this study, we determined circulating levels of C-reactive protein, several cytokines, chemokines, adhesion molecules and angiogenic factors along with those of leptin in healthy non-pregnant and pregnant women and preeclamptic patients, and investigated whether serum leptin levels were related to the clinical characteristics and measured laboratory parameters of the study participants. Methods Sixty preeclamptic patients, 60 healthy pregnant women and 59 healthy non-pregnant women were involved in this case-control study. Levels of leptin and transforming growth factor (TGF)-beta1 in maternal sera were assessed by ELISA. Serum levels of interleukin (IL)-1beta, IL-1 receptor antagonist (IL-1ra), IL-2, IL-4, IL-6, IL-8, IL-10, IL-12p40, IL-12p70, IL-18, interferon (IFN)-gamma, tumor necrosis factor (TNF)-alpha, interferon-gamma-inducible protein (IP)-10, monocyte chemotactic protein (MCP)-1, intercellular adhesion molecule (ICAM)-1 and vascular cell adhesion molecule (VCAM)-1 were determined by multiplex suspension array. Serum C-reactive protein (CRP) concentrations were measured by an autoanalyzer. Serum total soluble fms-like tyrosine kinase-1 (sFlt-1) and biologically active placental growth factor (PlGF) levels were determined by electrochemiluminescence immunoassay. For statistical analyses, non-parametric methods were applied. Results There were significant differences in most of the measured laboratory parameters among the three study groups except for serum IL-1beta and TGF-beta1 levels. Serum leptin levels were significantly higher in preeclamptic patients and healthy pregnant women than in healthy non-pregnant women. Additionally, preeclamptic patients had significantly higher leptin levels as compared to healthy pregnant women. Serum leptin levels were independently associated with BMI in healthy non-pregnant women. In healthy pregnant women, both BMI and serum CRP concentrations showed significant positive linear association with leptin levels. There were significant positive correlations between serum leptin concentrations of healthy pregnant women and systolic blood pressure, as well as serum levels of IP-10, while their serum leptin levels correlated inversely with fetal birth weight. In preeclamptic patients, a significant positive correlation was observed between serum concentrations of leptin and IP-10. Furthermore, elevated serum leptin level and sFlt-1/PlGF ratio had an additive (joint) effect in the risk of preeclampsia, as shown by the substantially higher odds ratios of their combination than of either alone. Conclusions Simultaneous measurement of leptin with several inflammatory molecules and angiogenic factors in this study enabled us to investigate their relationship, which can help to understand the role of circulating leptin in normal pregnancy and preeclampsia.